Brittle-ductile transitions in vanadium and iron-chromium - Joseph, T; Tanaka, M; Wilkinson, A; Roberts, S (Elsevier, 2007)
We report ongoing experimental work on fracture and brittle-ductile transitions in vanadium, iron and iron-9% chromium single crystals and polycrystals. Tests were carried out by four-point bending of pre-cracked specimens in the temperature range 77-300 K, at a variety of strain rates. For a given material, variation of the brittle-ductile transition temperature with strain rate allows us to estimate an activation energy for the controlling process; for vanadium this was found to be similar to-0.37 eV, for iron similar to 0.21 eV and for iron-9% chromium similar to 0.11 eV.